Interaction between the tumor microenvironment and resection margin in different gross types of hepatocellular carcinoma. Issue 4 (27th October 2019) - Cha, Sung Whan; Sohn, Joon Hyung; Kim, Sung Hoon; Kim, Yun Tae; Kang, Seong Hee; Cho, Mee‐Yon; Kim, Moon Young; Baik, Soon Koo
Abstract: Background and Aim: There is no consensus regarding the safe resection margin in hepatocellular carcinoma (HCC). Several studies reported that different gross types require different resection margins. We investigated the changes in the tumor microenvironment (TME) in different gross types of HCC. Methods: We selected tumor tissue and normal tissue 1 and 2 cm away from the HCC. We analyzed the expression status of TME genes and the correlation between TME genes and the effective resection margin. We further divided the patients into two groups: group 1 included expanding and vaguely nodular types, whereas group 2 included nodular with perinodular extension, multinodular confluent, and infiltrative types. Results: Group 2 showed 27% and 45% 5‐year disease‐free survival (DFS) and overall survival (OS) rates, respectively. Group 2 was a significant prognostic factor for DFS and OS. In cases with a resection margin of less than 1 cm or more than 2 cm, there were no differences in recurrence and survival rate between the two groups. Group 1 patients who had a resection margin that ranged from 1 to 2 cm showed significantly better DFS and OS rates. β‐Catenin and matrix metalloproteinase 9 expression was significantly decreased and that of E‐cadherin was significantly increased according to the resection margin in group 1. Conclusions: Patients with expanding and vaguely nodular HCC may safely undergo surgical resection with a narrow resection margin, and patients with the other gross types must undergo surgical resection with more than a 2‐cm resection margin because of their TME conditions.